Psychological Impact of the Gaza Blockade: A Mental Health Analysis 2007–2024 - M. Agung Rahmadi; Luthfiah Mawar; Nabila Salsa Amri; Syifa Putri Ramlan; Rifqi Riyadhul Jinan; Helsa Nasution; Nurzahara Sihombing; Annisa Br Bangun; Nafiza Rizky Ramadhani Lubis (PPNI UNIMMAN, 2026)
This meta-analysis systematically examines the psychological effects of the Gaza blockade on the mental health of affected populations, synthesizing data from 47 studies with 31,842 participants published between 2007 and 2024. The results show a significant increase in mental health disorders, with a pooled effect size of r = 0.73 (95% CI [0.68, 0.78]). PTSD was the most prevalent at 73.2%, followed by depression at 68.7%, and anxiety at 65.4%, highlighting the severe psychological impact. Hierarchical regression analysis revealed a strong correlation between the duration of the blockade and the severity of psychological symptoms (β = 0.68, p < .001). Children and adolescents were particularly vulnerable, with an odds ratio of 2.84 for developing complex trauma. Structural equation modeling indicated that limited access to mental health services significantly worsened psychological conditions, with model fit indices (χ2/df = 2.34, CFI = 0.96, RMSEA = 0.058). This study also identified a higher prevalence of disorders compared to previous studies and uncovered a new pattern of intergenerational trauma (d = 0.82). This meta-analysis enhances the understanding of how prolonged blockades affect mental health and provides a foundation for evidence-based psychosocial interventions.